ChemInform Abstract: Selective Elaboration of Aminodiols Towards Small Ring α‐ and β‐Amino Acid Derivatives that Incorporate an Aziridine, Azetidine, or Epoxide Scaffold. Issue 31 (14th July 2016) - Semina, Elena; Zukauskaite, Asta; Sackus, Algirdas; De Kimpe, Norbert; Mangelinckx, Sven
Abstract: The osmium‐catalyzed dihydroxylation of aminomethylacrylates (I) affords functionalized diols of type (II) which are elaborated to yield 2‐(aminomethyl)oxirane‐2‐carboxylates, aziridine‐2‐carboxylates, and azetidine‐3‐carboxylates.